BIG DATA PIPELINE INFRASTRUCTURE DESIGN IN MSME E-COMMERCE SYSTEMS WITH A FOCUS ON DATA SOURCE PROCESSING USING ORCHESTRATION TOOLS - Wibowo, Isro' Rizky; Sani, Ramadhan Rakhmat; Dewi, Ika Novita; Alzami, Farrikh; Rizqa, Ifan; Salam, Abu; Irawan, Candra; Aqmala, Diana (Departemen Teknik Elektro, Universitas Diponegoro, 2024)
In the digital era, Micro, Small and Medium Enterprises (MSMEs) need to utilize data to improve their business performance, such as increasing customer targets, product development and pricing strategies. Apache Airflow is a powerful tool for building data scraping pipelines that are scalable, flexible, and easy to monitor. One of them is the Central Java MSME data scraping pipeline, which collects business registration information, business type, location, contacts, products, and financial information from various websites, including the Central Java Provincial Government website, basic goods price comparison tables, and specialized news sites. The captured data is stored in a data warehouse for further analysis by the Central Java souvenir entrepreneurs association (ASPOO) in the region. Apache Airflow is used to manage the scraping pipeline in the Central Java MSME E-Commerce system and ensure it runs smoothly. Apache Airflow also has a built-in dashboard for monitoring pipelines and troubleshooting issues. Overall, scraping pipeline in the Central Java MSME e-commerce system is a valuable tool for collecting and analyzing data on the MSME sector in Central Java. This pipeline is scalable, flexible and easy to use, and can be adapted to different user needs and can be integrated with various systems.